Unleashing Legal Polycentricity in Europe? Barnett, Hayek, and the Theory of European Union Law - Gauderie, Sébastien (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
The questioning of the public and monopolistic production of European Union law is extremely little, if at all, addressed by European Union legal theory. The article proposes to divide the reasons for this absence into two classes. The first part of the article explores reasons endogenous to European Union law. The second part is devoted to reasons that are part of the evolutionary context of European Union law, stemming from facts of a historical, political, epistemological and societal nature. The article suggests to refer to the theory of constitutional polycentric order developed by the American legal theorist Randy Barnett, as well as Friedrich Hayek's theory of interstate federation proposed as early as 1939. Despite the apparent difficulties presented by the Union's contemporary organization, mechanisms specific to European Union law and European culture are capable of supporting the rehabilitation of polycentric conception of Union law and Hayekian interstate federation.